Triple confusion: An interesting case of proteinuria in pregnancy - Pramod K Guru; Devon M Ramaeker; Arundhathi Jeybalan; Nirav A Shah; Sheldon Bastacky; Kelly V Liang (Saudi Journal of Kidney Diseases and Transplantation, 2016)
Pregnancy-related renal diseases are unique and need special attention, both for diagnosis and management. The major confounding factors for diagnosis are the physiological multiorgan changes that occur throughout the gestational period. Proper diagnosis of the renal disease is also important, given the impact of varied management options both on the maternal and fetal health. A young middle-aged female with a long-standing history of diabetes presented to the hospital with worsening proteinuria in her second trimester of pregnancy. Clinical history, examinations, and laboratory analysis did not give any clues for diagnosis of a specific disease entity. This led us to take the risk of renal biopsy for a tissue diagnosis. The odds of renal biopsy favored the management decision in her case, thereby avoiding the confusions prior to biopsy. The pathological diagnosis is a surprise though not a unique entity on its own (minimal change disease in pregnancy). The case illustrates the disparity of clinical presentations and the pathology in patients, and the importance of renal biopsy in pregnant patients in particular.